Cerebellar hemorrhage after resection of frontal meningioma - Danil Adam; Ioana Hornea; Raisa Croitoru (Romanian Neurosurgery, 2013)
Introduction: Remote cerebellar hemorrhage is an infrequent complication, potentially harmful with an unclear etiologic mechanism. There may be incriminated multiple risk factors: arterial hypertension, use of antiplatelet medication (Aspenter), CSF aspiration or drainage associated with intracranial hypotension. Material and methods: We present a 69 year old woman with remote intracerebral hemorrhage that occurred after frontal parasagittal meningioma resection. Results: An inadequate oral hydration was responsible for decreased level of consciousness, cerebellar and parietal-occipital cortical-sub-cortical contra-lateral hemorrhages. Close monitoring of water balance and adequate hydration is related to clinical improvement and resolution of brain imaging. Conclusion: Retraction of the brain due to intracranial hypotension led to some small vessels rupture and development of remote cerebellar hemorrhage.